IMPLEMENTASI FUNGSI LEGISLASI DPRD KABUPATEN SUMBAWA BARAT DALAM PEMBENTUKAN PERATURAN DAERAH - AFRILIANA, NOFI; UMAR, UMAR; KHADAFIE, MUAMMAR (GANEC SWARA, 2023)
The aims of this research are; 1) to analyze the legislative function of the West Sumbawa Regency DPRD based on Law Number 17 of 2014 concerning the MPR, DPD, DPR and DPRD. 2) to analyze public perceptions regarding the implementation of the legislative function of the West Sumbawa Regency DPRD in the formation of Regional Regulations. This research is a qualitative descriptive study. Data collection techniques use questionnaires, interviews, observation and documentation. Data were analyzed using a qualitative analysis approach. Based on the data obtained, the results of the research are that the legislative function of the West Sumbawa Regency DPRD in the process of making regional regulations is based on legal provisions. The West Sumbawa Regency DPRD has carried out its role in forming Regional Regulations (Perda) well. There are positive indications that the West Sumbawa Regency DPRD has accommodated the aspirations and needs of the community through a process of formulating regional regulations that is transparent and involves public participation. The DPRD has demonstrated a commitment to understanding community needs and prioritizing public participation in the process of formulating regional regulations. These results reflect positive efforts in implementing the principles of transparency and participation in the legislative process.